2017
DOI: 10.1038/bmt.2016.348
|View full text |Cite|
|
Sign up to set email alerts
|

Haploidentical transplantation with post-infusion cyclophosphamide in advanced Hodgkin lymphoma

Abstract: We investigated the use of haploidentical hematopoietic stem cell transplantation (haplo-HSCT) in the treatment of advanced Hodgkin lymphoma (HL). Sixty-two consecutive HL patients underwent haplo-HSCT. Unmanipulated stem cells and post-transplant cyclophosphamide were given to all patients as GVHD prophylaxis. At 100 days, the cumulative incidence of grades 2-3 and grades 3-4 acute GVHD was 23% and 4%, respectively. The chronic GVHD (cGVHD) cumulative incidence was 16%, with one patient experiencing severe cG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 31 publications
3
23
0
1
Order By: Relevance
“…Interestingly, an advantage in survival and progression-free survival of PBSC over BM has been recently reported in 62 patients receiving a haploidentical transplant for advanced Hodgkin disease. 26 The biology of this disease and its sensitivity to the immunological effect mediated by the haploidentical cells, may in part explain this finding. Bashey et al 13 reported comparable OS and mortality between BM and PBSC recipients in a large series of patients with lymphoid and myeloid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an advantage in survival and progression-free survival of PBSC over BM has been recently reported in 62 patients receiving a haploidentical transplant for advanced Hodgkin disease. 26 The biology of this disease and its sensitivity to the immunological effect mediated by the haploidentical cells, may in part explain this finding. Bashey et al 13 reported comparable OS and mortality between BM and PBSC recipients in a large series of patients with lymphoid and myeloid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Haplo‐identical HSCT with T‐cell replete grafts and post‐transplant cyclophosphamide‐based GvHD prophylaxis has contributed to favorable outcomes; however, this regimen has been associated with severe HC in the early post‐transplant period, especially in patients with delayed immune reconstitution. We demonstrated that patients having virus‐associated HC in the early post‐transplant phase can develop virus‐specific T cells, and this was associated with viral clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Every patient provided informed consent. Nineteen patients were included in previous manuscripts [8][9][10]. Inclusion criteria were: lack of HLA-matched related or unrelated donor; primary refractory or relapsed HL refractory to conventional second-line salvage chemotherapy.…”
Section: Methodsmentioning
confidence: 99%